2014
DOI: 10.1186/1423-0127-21-15
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of a sesamin derivative, 3-bis (3-methoxybenzyl) butane-1, 4-diol on ischemic and hypoxic neuronal injury

Abstract: BackgroundStroke is one of the leading causes of neuronal death. Sesamin is known for neuroprotection by its antioxidant and anti-inflammatory properties but it lacks blood–brain barrier (BBB) activity. A panel of sesamin derivatives was screened and 3-bis (3-methoxybenzyl) butane-1,4-diol (BBD) was selected for high BBB activity and tested for its neuroprotective effect.MethodsThe focal cerebral ischemia of Sprague–Dawley rats and hypoxia models of murine BV-2 microglia or PC12 cells under oxygen/glucose depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…BV-2 cells were pretreated with KHG26792 for 30 min followed by hypoxia for 24 h. The results of this assay demonstrated a 49% reduction in cell viability 24 h after hypoxia ( Fig. 1A ), which is in agreement with previous observations ( 2 , 10 ). However, 50 μM KHG26792 rescued cells from hypoxia-induced toxicity to near normal viability levels ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…BV-2 cells were pretreated with KHG26792 for 30 min followed by hypoxia for 24 h. The results of this assay demonstrated a 49% reduction in cell viability 24 h after hypoxia ( Fig. 1A ), which is in agreement with previous observations ( 2 , 10 ). However, 50 μM KHG26792 rescued cells from hypoxia-induced toxicity to near normal viability levels ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have reported that hypoxia–ischemia-induced apoptosis in the brain is evident by the activation of caspase-3 ( 10 ). We further examined the effects of KHG26792 on the levels of caspase-3 as hypoxia is known to promote cell death through a caspase-3 dependent pathway ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that a good neurotherapeutic drug should be able to pass the blood-brain barrier (BBB) to reach the brain target site [45]. Many studies have showed that lignans containing typical aromatic rings can cross the BBB [46].…”
Section: Discussionmentioning
confidence: 99%
“…Combining the results of bioinformatics analysis and in vivo studies, we assumed that lignans in KL played roles as the main ligands of the 5-HT1AR. It is well known that a good neurotherapeutic drug should be able to pass the blood-brain barrier (BBB) to reach the brain target site [ 45 ]. Many studies have showed that lignans containing typical aromatic rings can cross the BBB [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although many adverse outcomes occur once the BBB is permeable, there are experimental studies that show that stabilizing the BBB and reducing inflammatory markers after hypoxic ischemic events as well as HIE may be beneficial [ 36 , 37 , 38 , 39 , 40 ]. For example, a study exploring the mechanisms of granulocyte-colony stimulating factor (G-CSF) as a treatment after a neonatal rat model of HIE, demonstrated that G-CSF elicited BBB stabilization by G-CSF receptor stimulation and activation of the phosphoinositide 3-kinase (PI3K)/Akt pathway.…”
Section: Potential Intervention Targetsmentioning
confidence: 99%